Understanding the “General Principles of Food Hygiene” (including GHP and HACCP) published in 2020 by Codex Alimentarius, and its applications on food industry and catering in Taiwan - Chiang, I-Yuan; Hsu, Chia-Ho; Lin, Meng-Yu (Open textbook library., 2021)
The Codex Alimentarius published a new version of ‘’General Principles of Food Hygiene’’ in November 2020. The series of the document has been critical for countries/organizations to develop and revise their food regulations/certifications. Thus, the new release will trigger revisions on food regulations/certifications. We translated ‘’General Principles of Food Hygiene’’ and added food regulations and GHP/HACCP examples from Taiwan to this book. Therefore, it could be a nice stepping stone to understand food regulations and the food industry in Taiwan.